Analisis Pemahaman Konsep, Multirepresentasi, dan Kosistensi Jawaban Siswa SMA pada Konsep Hukum III Newton - Nur Utami Amaliah*; Endang Purwaningsih (Universitas Syiah Kuala, 2021)
Newton's third law is a fundamental concept of Physics that is still not reached by students. The tendency of students who do not understand the concept well can be observed by measuring the ability of multi-representation and solutions when solving Physics problems. Therefore, this study aims to determine the concept of Newton's third law understood by students, the multi-representation students have, and the consistency of students' answers in answering physics questions. The participants numbered 28 students from the second semester of high school, selected using the purposive sampling technique, who had just completed discussions about Newton's Law and were willing to participate in this study. Participants were given 6 two-tier question items that managed the R-FCI questions. The results of the answers were analyzed quantitatively to determine the initial percentage description and then analyzed qualitatively to determine understanding, multi-representation ability, and consistency in depth. Most of the participants had low conceptual understanding and answered the questions consistent-wrong. However, based on the analysis of the answer choices and the reasons given, most students understand the meaning of the representation of the answers given